Pengembangan Media Pembelajaran Menggunakan Aplikasi Prezi pada Bidang Studi IPS Materi Kedatangan Bangsa Eropa Ke Indonesia Kelas VIII SMP - Yunaldi Yunaldi; Zuwirna Zuwirna (Jurnal Family Education, 2023)
This study aims to produce a product in the form of Prezi application learning media. This type of research is development research known as Research and Development (R&D), the development model used is the ADDIE model. The development procedures in this study consisted of 5 stages, namely analysis, design, development, implementation and evaluation. The research instruments used were questionnaires, documentation, and assessment formats. Based on the results of the material validation, a value of 4.78 was obtained "Very Eligible" so that the material was declared fit for use, the results of the media validation I obtained a value of 4.5 "Very Eligible" and the validation of media experts II obtained a value of 4.65 "Very Eligible", so media is categorized as feasible to try. Furthermore, students' practicality trials obtained a value of 4.38 "Practical". Thus it can be concluded that Learning Media Using the Prezi Application in Social Science Subjects in Class VIII SMP is feasible and practical to use.